El impacto de la industria petrolera en la economía mexicana - Sánchez, Rafael A. (Estudios Internacionales, 1999)
This paper presents an analysis of the development of the oil industry in Mexico and its importance for the economic development of this country. First, the development of said industry from its beginnings at the end of the last century to the 1970s is analyzed. Second, the relationship between the oil industry and the foreign policy followed by Mexico is analyzed, where Oil has been used by the governments of that country as an instrument of foreign policy through which it has sought to achieve national objectives in international politics. Finally, the last section analyzes the role of oil in the forging of the economic crisis that Mexico has suffered since 1980 and its role in the current process of trade liberalization and structural adjustment of the economy.